THE ANALYSIS OF DEVELOPER EXPERIENCE IN THE KPR APPLICATION PROCESS THROUGH THE BTN PROPERTY FOR DEVELOPER APPLICATION AT THE BTN MANADO BRANCH - Erlangga Kurnia Pratama Moha; Indrie Debbie Palendeng; Ferdinand J Tumewu; Magdalena Wullur; Merlyn Mourah Karuntu; Shinta Jeanete Camelia Wangke (PT. Jurnal Center Indonesia Publisher, 2026)
This study analyzes the use of the BTN Properti for Developer application in the Home Ownership Credit (KPR) application process at Bank BTN Manado Branch using the Technology Acceptance Model (TAM) and User Experience (UX) approaches. The study used a descriptive qualitative method through in-depth interviews with four developer users of the application. Data analysis was conducted using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results show that the BTN Properti for Developer application is generally well received by developers because it is considered easy to use, has a clear application flow, and is able to improve the efficiency of time, costs, and energy through a digital process. However, several obstacles were still found, such as limited document upload size, navigation that is not fully intuitive, and delays in status updates outside of operating hours. Support from BTN was considered quite responsive through training and direct communication, although improvements in the communication features in the application are needed. Based on the TAM analysis, application acceptance is influenced by perceptions of usefulness and ease of use, while from a UX perspective the application shows good usability and usefulness quality, but still requires development in the aspects of interactivity and accessibility. This study concludes that the BTN Properti for Developer application plays an important role in supporting the digital transformation of mortgage applications, with a note that continuous development is needed to optimize services and be user-oriented.